Sistema De Riego Automatizado Para La Huerta Escolar Del Colegio Victorioso (2023)
Irrigation has been one of the means most used by farmers, an ancient practice, developed in order to provide an adequate amount of water for the proper development of crops and thus allow a high production of food of excellent quality. The purpose of this work is the implementation of a prototype of an automated irrigation system using humidity sensors to facilitate the irrigation process of the school garden of the Victorioso School in the city of Villavicencio, Department of Meta. With the main objective of minimizing the use of water resources in a more favorable way by the students of the institution, in which there is no waste of water, also using a Raspberry PI microcomputer, through a closed loop control system. Key words: School garden, Humidity sensors, Water resource, closed loop control system, Raspberry PI.